Płynność, autentyczność, słabość – paradygmaty ponowoczesnej religijności (Przegląd Religioznawczy – The Religious Studies Review, 2025)
The characteristic features of postmodernism – such as anti-dogmatism, the subjectivisation of knowledge, the affirmation of individual autonomy, the emphasis on personal religious experiences and the aestheticisation of reality – also extend to the sphere of spirituality and religiosity. Questioning modern metaphysical and historical narratives requires the formulation of new guiding categories that will be able to capture the contemporary human condition. It seems that in the context of postmodern culture, categories such as fluidity and temporariness are increasingly seen as constitutive of contemporary forms of religiosity, gradually replacing the traditional attributes of stability, permanence and absoluteness.